Effect of Polyethylene Molecular Architecture on the Dynamic Viscoelastic Behavior of Polyethylene/Polyhexene-1 Blends and Its Correlation with Morphology. Issue 5 (24th March 2019) - Jozaghkar, Mohammad Reza; Jahani, Yousef; Arabi, Hassan; Ziaee, Farshid
ABSTRACT: In the present work, the rheology, morphology, and interfacial interaction of polyethylene/polyhexane-1 (PE/PH-1) blends with various polyethylene types with different molecular architectures are investigated. The scanning electron microscopy (SEM) images showed a droplet-matrix morphology in all percentage of PH-1 for all blend systems and the size of droplets increased proportionally with PH-1 content. The minimum droplet size is observed for high-density polyethylene (HDPE)/PH-1 blends. The homogeneity of the blends at various compositions is assessed by using viscoelastic parameters determined by dynamic oscillation rheometry in the linear viscoelastic region. A distinct Newtonian plateau at low frequencies is perceived and the variations of complex viscosity (η*) versus angular frequency (ω) for all blend systems are in good agreement with Carreau-Yasuda model. The complex viscosity of samples at various percentages of PH-1 showed the negative deviation from mixing rule in low and high frequencies for all blend systems. The Cole-Cole plots deviated from semi-circular shape at higher percentages of PH-1 than 10wt% in the blends of low-density polyethylene (LDPE)/PH-1 and linear low-density polyethylene (LLDPE)/PH-1. By using emulsion theoretical model, the lowest interfacial tension is found for HDPE/PH-1 blends comparing with its counterparts based on LDPE and LLDPE and the best fitting with experimental data was observed for this blends system. GRAPHICAL ABSTRACT: GRAPHICAL ABSTRACT